Analisis Pengaruh Kualitas E-Service Grab Terhadap Customer Satisfaction and Loyalty menggunakan E-S-QUAL dan E-RECS-QUAL - Iqbal Caraka Altino; Himawat Aryadita; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The rapid growth of the market share of e-commerce in Indonesia was already beyond a reasonable doubt. To deal with the intensity increasing challenges, the company in its business were required to think creatively to find a variety of breakthrough strategies that were able to create optimal synergy that contributes to the achievement of its objectives. In the industrial or business oriented customers quality of service was one of the factor that could affect customer satisfaction and loyalty. This research's goal is to know how influence the quality of service expecially e-service to customer satisfaction and customer loyalty in the Grab application user. The criteria of respondents in this research's questionnaire is a user that has done an online transaction using Grab application once transaction in minimum. Total sampel used in this research is 100 respondent chosen using simple random sampling methods. The model used in this research is adapted from Yang and Tsai wich used four latent variable: E-S-Qual, E-RecS-Qual, Online Satisfaction, dan Online Loyalty. The model then evaluated by using PLS-SEM. The research started by evaluating the model, Outer Model (Measurement Model) and inner model (Structural model). The result from this research is Online Satisfaction will have a significantly positive impact on Online Loyalty, Online satisfaction will be positively affected by E-S-Qual, Online satisfaction will be positively affected by E-RecS-QUAL, Online satisfaction will mediate the effects of E-S-QUAL on the online loyalty, and Online satisfaction will mediate the effects of E-RecS-QUAL on the Online Loyalty.